Still - Hall, Leila (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
This thesis is a novella in fragments set in contemporary Lesotho. It tells the story of a Mosotho woman in her 30s who has spent a long time living out of the country. She returns to search for a former lover who she hasn't seen for 15 years. The nonlinear narrative follows her journey, exploring a range of themes, including sexuality, gender and class relations, memory and time, relationship to place, non-conformity and defiance in the face of societal pressure and conformism. The style of writing is inspired by a diverse range of writers, including Sonallah Ibrahim for his understated, sparse and minimalist prose, Tina May Hall for her ability to tell a story in fragmented vignettes, Noy Holland for her understanding of time as synchronous and non-linear, and Ayi Kwei Armah for his skill in evoking the feelings, textures and specificities of a place.
Keywords: South African fiction (English) -- 21st century; Short stories, South African (English) -- 21st century